Avaliação do impacto do programa de controle da poluição do ar por veículos automotores e da frota em desacordo com o programa na saúde pública da Região Metropolitana de São Paulo - Leirião, Luciana Ferreira Leite [UNIFESP] (2018)
Objective: To evaluate the environmental and health impact of the fleet in disagreement with the actual phases of PROCONVE in the Metropolitan Region of São Paulo. Methods: We conducted a five-year interval analysis between 1985 and 2015 to verify the contribution of vehicles emissions to air quality. Using Aphekom method, we estimated the number of avoided deaths due to the decrease on emission of particulate matter on this period by vehicles. We also conducted bottom-up analysis to detach emissions from vehicles of different ages in 2014 and 2015. We projected a new scenario of emissions replacing those vehicles in disagreement with actual phases of PROCONVE for newer ones. Using the difference between the actual air quality and the one from the projected scenario, we estimated the years of life lost due to emissions by old vehicles. Results: The historical analysis indicated that PROCONVE effects could be noticed only from 1995 on. Between 1995 and 2015, air quality improved16 μg/m³ to particulate matter and it could be associated with 903 nonexternal avoided deaths. The separation of emissions by vehicles of different ages revealed that trucks and buses are the main responsible for particulate matter emissions. A scenario without vehicles in disagreement with actual phases of PROCONVE would decrease the PM10 concentration in 10 μg/m³ and PM2,5 concentration in 6 μg/m³. This air quality improvement could avoid more than 65,000 years of life lost due to air pollution between 2014 and 2015 and save more than US$ 4 bi. Conclusions: Old vehicle which circulate in Metropolitan Region of São Paulo are one of the biggest obstacles to PROCONVE success. The public health costs avoided with an air quality improvement due to retirement of old vehicles could finance change in transportation modes.